Phasing out Diploma in Nursing: Merits and Implications on Nursing Education in Pakistan - Hussain Maqbool Ahmed Khuwaja (Journal of the Pakistan Medical Association, 2021)
On 8th August, 2019, Pakistan Nursing Council announced the ceasing of the three year Diploma in Nursing which heralds a new era of the Bachelor of Science in Nursing (BScN) as the entry point for the nursing profession in Pakistan. This brings Pakistan in line with most developed and many developing countries. Continuous...